Leaf nutrient resorption differs among canopy and understory plant species in subtropical Eucalyptus and Acacia plantations. (24th March 2022) - Wang, Jun; Hui, Dafeng; Liu, Zhanfeng; Lin, Yongbiao; Wang, Faming; Long, Jing; Mou, Zhijian; Lu, Hongfang; Ren, Hai
Abstract: Although plants are known to conserve nutrients by resorbing them from senescing leaves, how resorption of foliar macro‐ and micronutrients is affected by plant growth form (e.g., trees, shrubs, and ferns) and forest age are not well understood. The current study was conducted in four subtropical monoculture plantations: Eucalyptus and Acacia plantations in 14 and 35 years old, respectively. Leaf resorption efficiencies (REs) and resorption proficiencies (RPs) of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and manganese (Mn) of the canopy trees and understory shrubs and ferns were determined. N, P, and K but not Ca and Mn were generally resorbed from senescing leaves. RE was significantly higher for P than N, indicating that P was more limiting than N in the subtropical plantations. Nutrient REs did not differ with plantation age, while nutrient RPs generally tended to be lower in the 14‐year‐old than in the 35‐year‐old plantations. REs significantly differed among canopy and understory plant species with different growth forms, that is, NRE, PRE, and KRE values were much higher in woody plants (especially the canopy tree species) than in ferns. REs were correlated with foliar nutrient concentrations but not with soil nutrient concentrations. Our findings suggest that resorption of nutrients from senescing leaves differs among canopy and understory plants, and implicate that introducing native tree species into these plantations could be implemented for accelerating the community succession and further improving the multifunctionality.